Inhaled steroids and airway remodelling in asthma - Chetta, A.; Marangio, E.; Olivieri, D. (Acta Biomedica Atenei Parmensis, 2003)
Bronchial asthma is a chronic inflammatory disease characterized by inflammatory cell infiltration and by some long-lasting structural changes of bronchial wall, defined as airway remodelling. Airway remodelling can significantly affect two important functional characteristics of asthma, i.e. airway hyperresponsiveness and bronchial obstruction reversibility. Airway remodelling might be responsible for most of the inter-individual variability of bronchial hyperresponsiveness and might also determine the irreversible component of the airway obstruction, sometimes detectable in asthmatic patients. Among anti-asthma drugs, inhaled steroids are the most effective on inflammation and remodelling of airway wall. Recent evidences indicate that high doses of inhaled corticosteroids can significantly reduce not only inflammatory cells but also some components of airway remodelling, such as the increased airway wall vascularity and the basement membrane thickness. Conversely, low doses of inhaled corticosteroids can significantly act only on airway cell infiltration.